Double-rowed teeth: design specialization of the H. venator ants for enhanced tribological stability. (26th July 2021) - Zhang, Wei; Wu, Zhigang; Wang, Zixin; Wang, Zhe; Li, Chuchu; Rajabi, Hamed; Wu, Jianing
Abstract: The ant H. venator can engage in various labors using a pair of elongated mandibles with the ability to rotate about two orthogonal axes. This biaxial rotation enables the ant to gently handle their small, fragile eggs with enhanced contact area and smaller work space. However, how this biaxial rotation influences the ant's predation ability and how the ant responds to this influence remain elusive. We quantitatively investigate the tribological performance of the ant's mandibles during interactions with prey by taking morphology and kinematics into consideration. We find that each ant mandible features unique, double-rows of dorsal teeth (DT) and ventral teeth (VT), which are employed to firmly clamp prey over a wide range of sizes by biting their different body parts, demonstrating the ant's predation ability. We hypothesize the mechanism underlying such an ability may rely on the two, non-parallel rows of teeth which potentially eliminate effects of biaxial rotation. To test this hypothesis, we systematically change the distribution and orientation of teeth on bio-inspired robotic mandibles and investigate the mandible tribological performance of different teeth configurations. We find that the friction coefficient varies prominently between the DT and VT resulting from biaxial rotation, with the variations showing an inverse pattern. This explains the observed phenomenon that mandibles equipped with DT and VT provide the most stable friction coefficient when clamping objects of different sizes using different mandible regions. The specialized distribution of teeth facilitates enhanced tribological stability in capturing prey, and demonstrates an intrinsic link between the form, motion, and function in the insect appendages. Our research sheds lights on the current understanding of the predation behaviors of ants, and can inspire future design of multifunctional robotic grippers.